American tough : the tough-guy tradition and American character - Wilkinson, Rupert (New York : Pereninial Library, 1986)
Reprint. Originally published: Westport, CT Greenwood Press, 1984
Ibcludes appendix, notes, bibliography and index
Keywords: National characteristics, American; Toughness (Personality trait); Personality and culture -- United States -- History; United States -- Popular culture